Thematic study of selected short stories of Mansha Yad - Latif, Amtul; Ishafaq, Humaira (sourcecoder, 2022)
Mansha Yad is a reliable reference in modern Urdu fiction. Their stories speak volumes about the development of thought and art. Such unique, untouched, thought-provoking and immersive stories of human dignity not only distinguish it from its contemporaries, but also give it a high place in the whole context of Urdu fiction. He has forged a new path between fantasy and factual narrative that resembles Chopal’s storytelling apart from the cities, but Mansha Yad’s narrative runs not only on the surface but also in depth. In that sense, they are separate and connected to the past. His stories are rooted in the towns of Punjab and are full of life in which there is centuries of simplicity and innocence and also the basic desires and contradictions of the man connected with the land. Mansha Yad is distinguished among his contemporaries in that he falls in love with urban characters and the process of peeking inside is part of his art.